The Three Nonnormative Traits (TNT) and (dis-)liking in work and nonwork settings - Dunlop, Patrick; Kerscher, F.; de Vries, R. E. (Elsevier, 2025)
Past research on the Three Nonnormative Traits (TNT) has shown that high versus low levels of HEXACO honesty-humility, agreeableness, and conscientiousness – but not emotionality, openness to experience, and extraversion – distinguish who we like from who we dislike in free-text descriptions. This study of 297 participants extends this work by comparing descriptions of liked and disliked targets from work settings to those from nonwork settings. We found conscientiousness descriptors strongly distinguished liked from disliked work targets, whereas honesty-humility and agreeableness were relevant to both target types. We also replicated one trait-similarity effect for openness to experience, but only in the nonwork context. Exploratory analyses generally showed only small differences in liking and disliking between different subtypes of targets within the work or nonwork context.